Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Perbankan: Studi pada Perbankan yang Terdaftar di BEI Tahun 2017-2019 - Muhammad Idris Ashari; Novita WeningTyas Respati; Muhammad Hudaya (Universitas Negeri Padang, 2023)
Financial performance of banking is an indicator that measures the successful or unsuccessful of a bank in carrying out its business activities and indicates that management has managed resources effectively and efficiently. Financial performance is proxied by the entity's profit growth. This study verifies and analyzes the influence of Non-Performing Loans, Loan to Deposit Ratio, Return on Assets, Operating Expenses, Operating Income, Inflation, Net Interest Margin, and Intellectual Capital on Financial Performance of Banking. Type of this research is associative. Population of this research is all around banks where listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. The sampling technique used was a census/sampling technique, total sample obtained was 41 banks. Hypothesis testing using multiple linear regression. The difference with previous research situated on the addition of the Net Interest Margin and Intellectual Capital variables. The Results of this research prove that NPL has a negative effect on financial performance. LDR, ROA, BOPO, Inflation, NIM, and IC have no effect on financial performance.